Sensores óticos a fibra aplicados à área de petróleo - Klemba, Francielli (2005)
This work describes the production of fiber Bragg gratings and long period gratings in optical fibers and their characterization as sensors devices in the detection of hydrocarbons that flow in pipelines, as well as its temperature measurement. The work was accomplished at Laser Laboratory of UTFPR. The long period gratings were produced using the point-to-point electric arc discharge technique from a splice machine and characterized as refractive index sensors of the fiber surroundings. The characterization was accomplished using different samples of alcohol, gasoline, turpentine, thinner, kerosene and naphtha. The biggest wavelength shift presented by the grating was 15.57 nm in the presence of the kerosene. The average refractive index grating sensitivity was 2.6x10-6 pm-1 in the range from 1.432 (thinner) to 1.448 (kerosene). This sensitivity relates to a smallest refractive index variation of 2.6x10-5 that can be measured, for an optical spectrum analizer with wavelength precision of ± 5 pm. The response time of the sensor was 3 seconds for the different samples used. The fiber Bragg gratings were characterized as temperature sensor devices of the samples. The gratings were produced both in SMF hydrogenated and photosensitive fibers, using an ultraviolet laser and a phase mask interferometer. The devices were characterized as temperature sensors, and a study for thermal stabilization of them was carried out. The obtained sensor sensitivity ranged from 10.2 nm/ºC up to 11.4 nm/ºC. As the precision of this type of sensor is related to the bandwidth of the fiber Bragg grating, a writing system technique based on a phase mask and an UV laser was implemented, making possible the writing of long and narrow bandwidth gratings.